Aortic lumen repair with glue-felt technique before proximal anastomosis in acute type a aortic dissection surgery - Muhammed Varol; Berk Arapi; Çiğdem Tel Üstünışık; Deniz Göksedef; Suat Nail Ömeroğlu; Gökhan İpek; Ozan Onur Balkanay (Journal of Cardiothoracic Surgery)
Abstract Objectives Despite the advances in medicine, aortic dissection remains a cardiac surgery emergency with high mortality and morbidity rates. This study examined the effects of the Glue + Felt technique, which uses biological glue and felt to repair the proximal anastomotic site, on the outcomes of patients with acute type A aortic dissection. Methods A total of 108 patients who underwent surgery for acute type A aortic dissection at our clinic between 2007 and 2020 were included in the study. The patients were divided into two groups: the "Glue + Felt Technique" and the "Bentall-De Bono" groups, based on the surgical technique used for the aortic root. The effects of these two techniques on the development of intraoperative and postoperative complications and survival rates were statistically analyzed. Results The Glue + Felt technique was used for 76 patients, while the Bentall-De Bono technique was used for 32 patients. The Kaplan–Meier analysis revealed significant differences in survival rates between the two groups over the entire follow-up period, both with and without propensity score matching (p < 0.001 and p = 0.02, respectively). However, no significant differences were observed in comparisons beyond the first 30 days of follow-up, either with or without propensity score matching (p = 0.573 and p = 0.561, respectively). The main factors contributing to this difference were the duration of cardiopulmonary bypass and aortic cross-clamp time (p < 0.05). During the average follow-up period of 46.2 ± 31.6 months, no re-intervention was required in patients from the Glue-Felt technique group. Conclusions The mortality rate in aortic dissection surgery is higher with more extensive surgical intervention as the duration of cardiopulmonary bypass and aortic cross-clamp time increases. Repairing the lumen and reducing operation time in suitable patients using the Glue-Felt technique for the proximal anastomotic site positively impacts postoperative complications and improves in-hospital and 30-day survival rates, without increasing long-term re-intervention rates.